Assessment of the efficacy and safety of a new complex skin cream in Asian women: A controlled clinical trial. (16th May 2017) - Jung, Yu Seok; Lee, Ji Hae; Bae, Jung Min; Lee, Dong Won; Kim, Gyong Moon
Summary: Background: Medical products such as hydroquinone and tretinoin have been widely used to treat various types of skin hyperpigmentation. However, these products are limited in daily use given their adverse effects. Other alternative agents with fewer adverse side effects have been developed. However, single agents often do not produce satisfactory results. Aims: To evaluate the efficacy and safety of a new brightening complex cream containing niacinamide, tranexamic acid, oxyresveratrol, glutathione disulfide, and linoleic acid. Patients and Methods: A total of 26 Korean women seeking to lighten their skin were enrolled. The product was applied on the face two times per day for 12 weeks. Standardized photographs were taken at baseline, 4 weeks, 8 weeks, and 12 weeks. Efficacy was assessed using melanin index (MI), erythema index (EI), and chromatic aberration values (L*, a*, and b*). Improvement perceived by investigators and patients was measured as well. Results: The L*‐value was increased at 8 weeks (0.7±2.5, P <.05) and at 12 weeks (0.8±2.5, P <.05). The MI was significantly decreased at 8 weeks (−4.2±4.5, P <.05) and at 12 weeks (−3.8±4.8, P <.001). The EI was significantly improved at 12 weeks (−3.2±2.2, P <.001). More than 80% of patients were considered improved at 12 weeks based on the view of the investigators and patients. Conclusions: The new brightening complex cream was proved to be effective and safe in Asian women.